Vershina – a Polish village in Siberia. Factors influencing language maintenance under changing social, cultural, economic and political conditions - Gluszkowski, Michal (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2011)
The article discusses factors influencing language maintenance under changing social, cultural, economic and political conditions of Polish minority in Siberia. The village of Vershina was founded in 1910 by Polish voluntary settlers from Little Poland. During its first three decades Vershina preserved Polish language, traditions, farming methods and machines and also the Roman Catholic religion. The changes came to a village in taiga in the1930s. Vershina lost its ethnocultural homogeneity because of Russian and Buryat workers in the local kolkhoz. Nowadays the inhabitants of Vershina regained their minority rights: religious, educational and cultural. However, during the years of sovietization and ateization, their culture and customs became much more similar to other Siberian villages. Polish language in Vershina is under strong influence of Russian, which is the language of education, administration, and surrounding villages. Children from Polish-Russian families become monolingual and use Polish very rare, only as a school subject and in contacts with grandparents. The process of abandoning mother tongue in Vershina is growing rapidly. However, there are some factors which may hinder the actual changes:the activity of local Polish organisations and Roman Catholic parish as well as folk group “Jazhumbek”